Teaching global history - Singer, Alan J., author.
1 online resource
Keywords: "This updated edition of Teaching Global History challenges prospective and beginning social studies teachers to formulate their own views about what is important to know in global history and why. This essential text explains how to organize curriculum around broad social studies concepts and themes, as well as student questions about humanity, history, and the contemporary world. All chapters feature lesson ideas, a sample lesson plan with activity sheets, primary source documents, and helpful charts, graphs, photographs, and maps. This new edition includes connections to the C3 framework, updates throughout to account for the many shifts in global politics, and a new chapter connecting past to present through current events and historical studies in ways that engage students and propel civic activism"--